Dyslipidemia a clinical approach - Myerson, Merle (Wolters Kluwer, 2019)
"Dyslipidemia: A Clinical Approach is intended as a low-cost, quick-reference, easy-to-navigate guide for a broad range of healthcare professionals that will provide high-yield decision-making tools to ensure confidence in patient treatment and management of those who are suffering from a lipids disorder or related disease. Content will include detailed drug tables, information on important drug interactions, and also non-statin alternatives for those patients who cannot tolerate statins. In addition, decision-making algorithms and careful patient management plans will be included to ensure quicker and more effective treatment and management of patients"--Provided by publisher.